2003
DOI: 10.1021/jp036105g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Gas-Phase Nitric Acid ton-Hexane Soot:  Thermodynamics and Mechanism

Abstract: The adsorption of gas-phase nitric acid on n-hexane soot was measured as a function of temperature, relative humidity (RH), and nitric acid partial pressure in a coated-wall flow tube coupled to an electron-impact mass spectrometer. The specific surface area (SSA) of the soot, determined from the BET isotherm of Kr at 77 K for each sample, was 88-372 times larger than the geometric surface area. The SSA increased linearly with soot mass for thin samples but saturated at high mass. For the most part, the nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
66
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(84 citation statements)
references
References 51 publications
(129 reference statements)
12
66
5
Order By: Relevance
“…However, the influence of adsorbed HNO 3 on Reaction (1) is still unclear. The conclusion, that Reaction (1) cannot account for atmospheric HONO formation is in good agreement with a model study in which the deactivation of the soot surface was taken into consideration (Aumont et al, 1999). Only in the case that a fast reactivation of the soot surface was proposed (Aumont et al, 1999), yet not observed in the laboratory, or when the well documented deactivation was ignored (Kotamarthi et al, 2001;Lary et al, 1999) a significant influence on the atmosphere was calculated.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, the influence of adsorbed HNO 3 on Reaction (1) is still unclear. The conclusion, that Reaction (1) cannot account for atmospheric HONO formation is in good agreement with a model study in which the deactivation of the soot surface was taken into consideration (Aumont et al, 1999). Only in the case that a fast reactivation of the soot surface was proposed (Aumont et al, 1999), yet not observed in the laboratory, or when the well documented deactivation was ignored (Kotamarthi et al, 2001;Lary et al, 1999) a significant influence on the atmosphere was calculated.…”
Section: Introductionsupporting
confidence: 79%
“…The formation of HONO in the reaction of HNO 3 on soot surfaces was also proposed in a model study by Lary et al (1999) and was observed in the reaction of soot with liquid HNO 3 solutions (Louisnard et al, 1995). However, in the more recent study of Aubin and Abbatt (2003) no formation of HONO was observed, although the authors could not determine the upper limit for the HONO yield, because of the missing calibration of their mass spectrometer. Although more recent studies point to the fact that the discrepancies of the modelled and measured NO x /HNO 3 ratio cannot be explained by Reaction (2) (e.g.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…10 Those species are emitted to the atmosphere from natural and anthropogenic sources with an average global emission rate of anthropogenic carbon from fossil fuel combustion as high as 2.4 × 10 10 kg per year. 11 Once liberated into the ambient environment, PAHs and soot in respirable size of 10-100 nm can be transferred into the lungs by inhalation and are strongly implicated in the degradation of human health, 12 particularly due to their high carcinogenic risk potential. PAHs and carbonaceous nanoparticles are also serious water pollutants of marine ecosystems and bioaccumulate in the fatty tissue of living organisms.…”
Section: Introductionmentioning
confidence: 99%